FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB-P2) DI KOTA TEGAL - Islami, Afita Din; Krisdiyawati; Kartika, Dewi (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2025)
This study analyzes factors influencing taxpayer compliance in paying Rural and Urban Land and Building Tax (PBB-P2) in Tegal City. PBB-P2 compliance in Tegal City was low, characterized by minimal participation in socialization activities and low taxpayer understanding of tax procedures and obligations. The research aimed to identify the impact of tax knowledge, tax service, tax sanctions, and tax rates on taxpayer compliance. A quantitative approach was employed, collecting data from 100 PBB-P2 taxpayer respondents via questionnaires using accidental sampling. Data analysis utilized multiple linear regression after validity, reliability, and classical assumption tests. Results indicated that tax knowledge and tax sanctions had a positive and significant effect on compliance. However, tax service and tax rates partially showed no significant effect. Simultaneously, all four factors significantly influenced compliance, explaining 51.8% of the variation. Recommendations include enhancing education and enforcing sanctions for improved compliance. Evaluation of services and rates remains crucial. Further research can explore other factors for a more holistic understanding. Keywords: PBB-P2, Tax Compliance, Tax Sanctions, Taxpayer Knowledge